Co-situation of Using Sonki in Gum Arabic Production in Abu Zabad Locality, West Kordofan State, Sudan - Muneer Elyas Siddig Eltahir; Elsharif Musa Ishag Ahmed; Seif Aldin Dawina Abdallah Faragallah; Musa, Faisal Ismail; Ahmed Abdallah Adam Mohamed (Talenta Publisher, 2025)
This study investigated the adaptation and use of the Sonki tapping tool for gum Arabic production from Acacia senegal in Abu Zabad locality, West Kordofan, Sudan. Data were collected from 140 randomly selected producers (63 % of the total producersâ€™ population) using structured questionnaires and 11 focus group discussions. Descriptive statistic and Chi-square tests were conducted using SPSS, OriginPro 2024b, and Microsoft Excel. Results indicated that 78.6 % of respondents practiced farming alongside gum Arabic production, predominantly as an inherited tradition. About 72.9 % tapped gum trees in October. However, awareness of the Sonki tools was reported by 62 % of respondents, with 52.9 % utilizing it. Although, the access to the Sonki tool was primarily through market (94.9 %), with a smaller portion obtaining it from the Forest National Corporation and NGOs. Further, provision and training was identified by 83 % of respondents as a critical factors in promoting adaptation. Chi-square analysis showed that significant differences (P â‰¤ 0.05) between years of experience, knowledge of Sonki and usage. The proportion of the producers owing and using Sonki was 72 %. Despite the access and knowledge barriers. The study concluded that while progress has been made, broader dissemination and adaptation are essential. The findings of study recommend that, facilitating access, promoting proper use, and emphasizing provision Sonki and training to ensure sustainable tapping practices.